A Novel Sutureless Integrated Stented (SIS) Graft Prosthesis for Type A Aortic Dissection: A Pilot Study for a Prospective, Multicenter Clinical Trial - Dai, Lu; Qiu, Jiawei; Zhao, Rui; Cao, Fangfang; Qiu, Juntao; Wang, De; Fan, Shuya; Xie, Enzehua; Song, Jian; Yu, Cuntao (Frontiers in Cardiovascular Medicine, 2022)
Aims: Various kinds of surgical strategies and prostheses have been advocated to improve short-term and long-term outcomes in type A aortic dissection (TAAD). Large-scale repair of the pathological aorta is hard to generalize due to complex procedures. We aimed to investigate the performance, effectiveness and safety of a novel Sutureless Integrated Stented (SIS) graft prosthesis in TAAD patients undergoing total arch replacement (TAR) and frozen elephant trunk (FET) implantation surgery. Methods: All patients admitted to Fuwai Hospital were prospectively screened. Urgent or scheduled surgery was arranged for eligible patients. The primary endpoint was operative mortality. Key secondary endpoints included stroke, spinal cord injury, unexpected aortic reoperation, and 1-year survival. Discharged patients were followed up with computed tomography angiography and transthoracic echocardiography at 3 months, 6 months and 1 year after surgery. Performance, effectiveness and safety analyses were performed in those patients. Results: Between August 1 and September 3, 2020, ten TAAD patients were enrolled in this study and successfully implanted with the SIS graft prosthesis. The median (IQR) age was 56.50 (43.75, 66.75) years (range from 31 to 75), and 7 patients were male (70.0%). All patients underwent ascending aorta replacement + TAR + FET and additional procedures when necessary. The median (IQR) operation time, cardiopulmonary bypass time and cross clamp time were 270.50 (218.50, 312.50), 110.00 (88.00, 125.75), 69.50 (51.25, 82.75) min, respectively. Of note, the median (IQR) circulatory arrest time was 9.00 (8.00, 9.00) min (range from 4 to 12). The median (IQR) lowest nasopharyngeal temperature was 26.75 (25.98, 27.67) ℃. Follow-up was 100% completed. During the 1-year follow-up, no patients died, no severe adverse events occurred, and rate of freedom from aortic reintervention was 100%. Conclusions: The SIS graft prosthesis was implanted in a novel sutureless way, which simplified the surgical procedure, shortened the circulatory arrest time and avoided deep hypothermia. The preliminary clinical outcomes and follow-up outcomes demonstrated the effectiveness and safety of this prosthesis. A large-scale trial is being conducted to further assess these findings.